Enterococcus faecalis V583 cell membrane protein expression to alkaline stress. Issue 1 (31st August 2022) - Cathro, Peter; McCarthy, Peter; Hoffmann, Peter; Kidd, Stephen; Zilm, Peter
Abstract: Enterococcus faecalis is able to adapt to alkaline conditions and is commonly recovered from teeth in which endodontic treatment has failed. The role that E. faecalis membrane proteins play in survival strategies to extreme alkaline conditions is unclear. We grew E. faecalis V583 in a chemostat at pH 8 and 11 at one-tenth the organism's relative maximum growth rate. Following membrane shaving, isotope-coding protein labels were added at the peptide level to samples and then combined. The relative proportion of membrane proteins were identified using LC-ESI mass spectrometry and MaxQuant analysis. Ratios of membrane proteins were log2 transformed, with proteins deviating by more than 1 SD of the mean considered to be up- or down-regulated. A total of six proteins were up-regulated in pH 11 including: EF0669 (polysaccharide biosynthesis family); EF1927 (glycerol uptake facilitator), and EF0114 (glycosyl hydrolase). A total of five proteins were down-regulated including: EF0108 (C4-dicarboxylate transporter); EF1838 (PTS system IIC component); EF0456 (PTS system IID component); and EF0022 (PTS mannose-specific IID component). In extreme alkaline conditions, the membrane proteins of E. faecalis seem to be involved in a shift of carbohydrate metabolism from the PTS system to glycerol, which supports the formation of a protective capsule protecting the cell. Abstract : Enterococcus faecalis cell membrane response to extreme alkaline conditions results in a shift of carbohydrate metabolism and supports the formation of a protective capsule.